Increase in serum concentrations of IgG2 and IgG4 by selenium supplementation in children with Down's syndrome. Issue 12 (December 1990) - Annerén, G; Magnusson, C G; Nordvall, S L
Abstract : In a previous study on children with Down's syndrome a reduced rate of infections was reported by their parents after the children had received six months' treatment with selenium supplements. In the present study the concentrations of the four IgG subclasses were measured in 29 of these children in samples of serum obtained before and immediately after the period of supplementation and one year after it had finished. Selenium had a significant augmentative effect on the serum concentrations of IgG2 and IgG4, but not of IgG1 and IgG3. This effect was not related to age, as among children over the age of 6 years the serum concentrations of IgG2 and IgG4 had decreased significantly one year after the treatment had been stopped. This study suggests that selenium has an immunoregulatory effect, which might be of importance in both basic research and clinical practice.